Factors Affecting Children's Sense of Identity with a Football Team - Rebge, Suleyman; Nevzat, Raziye (Sage Publications Inc, 2025)
This study explores how children form emotional and social identification with football teams through branding and digital engagement. Drawing on Social Identity Theory, the research investigates how brand-related stimuli influence the attachment and loyalty of children to sports teams. The study uses a qualitative design and semi-structured interviews with 20 junior football players (ages 10-12) from a professional academy in North Cyprus. Thematic analysis was employed to examine the data. Findings reveal four major themes: (1) attending live matches with family as an entry point for fandom, (2) strong emotional bonds with team identity shaped by brand image and perceived relationship quality, (3) expressions of brand identification including emotional reactions to team criticism, and (4) digital engagement through social media as a reinforcing mechanism for loyalty and belonging. These results demonstrate that children construct meaningful brand relationships shaped by social environments, peer influence, and online content. Despite its contributions, the study is limited by its reliance on self-reported interview data and a single-team sample, which may restrict generalizability. Future research should consider mixed-methods approaches and explore developmental and cultural differences in brand identification processes among youth.
Keywords: youth brand identification; peer influence; social media engagement; sports branding